Management of a Case of Chronic Suppurative Otitis Media with Homoeopathic Medicine Mercurius Solubilis - A Case Report (Advancements in Homeopathic Research, 2024)
Introduction: Chronic suppurative otitis media  (CSOM) is a long-standing infection of a part or  whole of the middle ear cleft characterized by  ear discharge and a permanent perforation. In  homoeopathy, there are various medicines having  a sphere of action on suppurative diseases. This is  a show case of Mercurius solubilise Homoeopathic  remedy for the case of CSOM: Mercurius solubilise is a black oxide of mercury. It affects the whole  system, penetrating every organ and tissue and also  has a wonderful effect on suppuration. Mercury, in  both acute and subacute forms, is the only drug that  effectively prevents suppuration.  Case summary: This is the case of 24 yr old man who  presented with CSOM and was successfully managed  with individualized Homoeopathic medicine, Mercurius Solubilis 200c. The case was followed  up with documentation of clinical symptoms and  investigation findings. In this article, the ultimate aim  is to provide the clinician with a homoeopathic tool in  the management of CSOM after having satisfactory  results in the case.
Keywords: Chronic Suppurative otitis media; Acute otitis media; Mercurius solubilise; Homoeopathy; Modified naranjo algorithm